Professional and Academic: Different Paces of Implementation? - Palomares, Ricard Calvo; Hernández , Juli Aguado; Signes, Enric Sigalat (Journal of Posthumanism, 2025)
This work explores the connection between academic education and professional practice in the scope of socio-labour auditing, proposing an innovative methodology that integrates two teaching models. With the fundamental participation of the Professional Association of Socio-Labour and Equality Auditing (CEAL) in the educational process and the obligation to carry out audits in companies with more than 50 employees (Royal Decree 902/2020), an empirical analysis was carried out by means of surveys to students (N=453) and professionals (282 audits). The student body reveals a positive perception of the usefulness of the subject, with average correlations with respect to the regulatory change. Professionals rate the obligatory nature of audits very positively. Although both assessments are positive, the students’ appraisal does not show a similar increase to that of working professionals. The main conclusion is that teaching innovations require a rhythm of their own, a considerable time to generate positive or desired effects.